AB0527 PREDICTIVE VALUE OF MIR200B-5P IN THE LYMPHOMAGENESIS IN SJÖGREN'S SYNDROME (SS): COMPARISON WITH THE PUBLISHED PREDICTION MODELS. PRELIMINARY RESULTS. (June 2019) - Kapsogeorgou, Efstathia; Protogerou, Athanase; Papageorgiou, Aristea; Voulgarelis, Michael; Tzioufas, Athanasios
Abstract : Background: miR200b-5p expression levels are decreased in the minor salivary glands of SS patients who have or will develop non-Hodgkin's lymphoma (NHL), discriminate them from those who will not (p<0.0001) and independently predicted NHL development (p<0.0001) 1 . Objectives: To compare the predictive performance of low miR200b-5p levels with the previously published multifactorial predictive models. Methods: 27 SS patients who didn't develop NHL during follow up (median follow up time upon biopsy performance, range: 8.9yrs, 1.33-14yrs) and 17 diagnosed with NHL during follow up (pre-lymphoma, median follow-up till lymphoma diagnosis, range: 3.67yrs, 0.42-8.5yrs) were studied. The multifactorial predictive models examined were: 1. Ioannidis et al 2 who defined patients expressing at least one of low C4 levels, salivary gland enlargement (SGE) and purpura as high-risk, 2. Baimpa et al 3 who designed 3 models (1, 2 and 3) based on the expression of at least 1, 2 or ≥3, respectively, of neutropenia, cryoglobulinemia, splenomegaly, lymphadenopathy and low C4 levels, 3. Quartuccio et al 4 who identified as high risk patients those having SGE and at least two of the following: low C4 levels, cryoglobulinemia, anti-La antibodies and leukopenia, and 4. Fragkioudaki et al 5 that defined as high-risk group those carrying ≥3 of the independent risk factors including SGE, lymphadenopathy, Raynaud phenomenon, anti-Ro/SSA and/or anti-La/SSB antibodies, rheumatoid factor positivity, monoclonal gammopathy and low C4 levels. Analyses were performed by estimating the area under the ROC curve (AUC), Kaplan-Meier (KM) lymphoma-free survival curves compared by the log-rank test, the positive and negative predictive values, sencitivity (Se) and specificity (Sp), as well as the PSEP index of the model intrinsic prognostic value 6 . Results: ROC analysis identified low miR200b-5p levels as the better prognostic tool from the other multifactorial models. Its predictive value was further supported by the other analyses (including PSEP index), where it ranked among the two best models, whereas it had the better combination of sensitivity and specificity (Table). Conclusion: Low miR200b-5p levels associated with the incidence of NHL in SS, exhibiting consistently higher values than the other multifactorial models; however, larger cohorts are required to verify its statistical and clinical significance. References: [1] Kapsogeorgou et al, Ann Rheum Dis 2018 [2] Ioannidis et al, Arthr Rheum 2002 [3] Baimpa, et al. Medicine 2009 [4] Quartuccio et al, J Autoim 2014 [5] Fragkioudaki et al, Medicine 2016 [6] Altman and Royston, Stat Med 2000 Disclosure of Interests: Efstathia Kapsogeorgou: None declared, Athanase Protogerou: None declared, Aristea Papageorgiou: None declared, Michael Voulgarelis: None declared, Athanasios Tzioufas Grant/research support from: ABBVIE, PFIZER, AMGEN, NOVARTIS, GSK